Pre-Evaluation of Industrialization Project of Local Science and Technology Achievements Based on FAHP - Yongzhi Chang; Yu Hang; Tong Liang (Discrete Dynamics in Nature and Society)
In order to build a scientific pre-evaluation system for the industrialization of local science and technology (sci-tech) achievements, based on the analysis of the characteristics and laws of the industrialization projects of sci-tech achievements, the pre-evaluation of the industrialization projects of sci-tech achievements at home and abroad, the importance of the pre-evaluation of the industrialization projects of local sci-tech achievements and the research methods, the pre-evaluation index system of industrialization projects of local sci-tech achievements has been established from six aspects: policy environment, technical performance, economic benefits, resource guarantee, organizational guarantee, and social benefits. The research took the smart manufacturing project in Xiqing District of Tianjin as the object of empirical analysis and applied the fuzzy analytic hierarchy process (FAHP) to comprehensively evaluate the project. The overall score of the smart manufacturing project was 87.639, and the evaluation result was good and in accordance with the actual situation. The feasibility and validity of the evaluation index system and the evaluation model are verified, the risks of economy and policy in the industrialization of sci-tech achievements are reduced, and the optimization rate of the industrialization project is improved, which provide a reliable basis for local governments to realize the industrialization of sci-tech achievements.